Efficient recovery process based on lead refining alkaline residues

By using NaOH solution leaching, mercaptolignin flocculation, and coconut shell wood fiber hydrogel adsorption of lead ions, combined with dilute nitric acid desorption and sodium carbonate precipitation, the high energy consumption and high cost problems in lead refining alkali slag recovery are solved, achieving efficient and environmentally friendly lead recovery.

CN120989389AActive Publication Date: 2025-11-21江西金德铅业股份有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511226122.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-29
Publication Date
2025-11-21
Estimated Expiration
2045-08-29

AI Technical Summary

Technical Problem

Existing technologies for lead refining alkali slag recovery suffer from high energy consumption, high costs, and difficulties in resource recycling. In particular, acid leaching leads to the co-dissolution of impurities and equipment corrosion, while electrolysis relies on precious metal electrodes and has high power consumption.

Method used

After leaching lead refining alkali residue with NaOH solution, coconut shell wood fiber hydrogel was prepared by combining mercaptolignin and polyacrylamide flocculation to adsorb lead ions. Lead was then recovered by desorption with dilute nitric acid and precipitation with sodium carbonate, avoiding damage from strong acid and high energy consumption from electrolysis.

Benefits of technology

It achieves highly selective lead recycling, reduces energy consumption and costs, improves lead recovery rate and purity, and the hydrogel is reusable, making it environmentally friendly and efficient.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120989389A_ABST
    Figure CN120989389A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of alkali residue recovery, in particular to an efficient recovery process based on lead refining alkali residues. Comprising the following steps that the lead refining alkaline residues are leached; flocculating the lead slag and preparing a lead mixed solution; preparing hydrogel for adsorbing lead; and recovering the lead by using the hydrogel adsorbing the lead. The hydrogel is prepared from coconut shells, cucurbituril and sodium alginate and used for adsorbing lead ions, a coconut shell wood fiber porous framework forms a three-dimensional through pore channel, rich groups on the surface provide physical adsorption sites, sodium alginate and Pb < 2 + > form a stable chelate through lone pair electrons, and the lead ions can be adsorbed through the stable chelate. Hydrophobic cavities of cucurbituril are embedded into the edges of micropores of wood fibers through Van der Waals force and matched with the diameter of hydration ions of Pb < 2 + >, the hydration Pb < 2 + > enters preferentially, and hydrogel and lead ions selectively capture each other, so that interference ions such as calcium and magnesium are effectively inhibited from competition, the content of lead in lead mixed liquid in the early stage is increased, and a foundation is laid for subsequent lead recovery.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of alkali residue recovery, and particularly relates to a high-efficiency recovery process based on lead refining alkali residue. BACKGROUND

[0002] The lead refining alkali residue is a high-risk solid waste generated in the process of lead electrolytic refining. In the molten state of crude lead, sodium hydroxide is added and air is blown in to make tin, antimony, arsenic and other impurities oxidize to form sodium salt, forming a low-melting-point dross. The dross layer is separated by mechanical scraping, and the lead refining alkali residue is obtained after cooling and solidification. Therefore, the lead refining alkali residue has a high lead content and also contains tin, zinc, silicon and other impurities.

[0003] The existing technology generally uses acid leaching method to recover the lead refining alkali residue. The acid leaching method uses simple equipment and has lower energy consumption than high-pressure or electrolysis process. However, a large amount of calcium, iron, zinc and other ions are co-dissolved while the lead is dissolved, which leads to heavy burden of subsequent purification. In addition, the strong acid environment destroys the structure of the adsorption material, and it is difficult to realize resource recycling. Another recovery method is to directly recover lead single element by electrolysis. The electrolysis method can selectively precipitate metal elements in the alkali residue by adjusting the current / voltage to control the redox strength, without using a large amount of chemical reagent. However, the electrolysis method relies on continuous direct current power supply, and the power consumption accounts for a high cost. In addition, the electrolysis method also needs noble metal electrodes or proton exchange membranes, which has high cost. Therefore, based on the characteristics of the lead refining alkali residue and the defects of the existing technology, the present application provides a new lead recovery process with high selectivity, low energy consumption and recyclability, to realize the resource utilization and harmless disposal of lead in the alkali residue, and to solve the problems existing in the prior art. SUMMARY

[0004] In view of the deficiencies in the prior art, the purpose of the present application is to provide a high-efficiency recovery process based on lead refining alkali residue.

[0005] A high-efficiency recovery process based on lead refining alkali residue, comprising the following steps: S1: leaching the lead refining alkali residue The lead refining alkali residue is soaked in a NaOH solution. After the reaction is completed, solid particles are filtered out using a 100-mesh stainless steel screen, and solid-liquid separation is performed to obtain leaching residue and leaching solution; S2: flocculating the lead residue and preparing a lead mixed solution The mercapto lignin powder is dissolved in deionized water to prepare a mercapto lignin solution. The mercapto lignin solution is stirred and activated, and then added to the leaching solution. The mixture is stirred, and a polyacrylamide solution is added. The mixture is stirred and centrifuged to obtain lead residue. The lead residue and the leaching residue are combined to obtain treated lead residue. The treated lead residue is immersed in a hydrochloric acid solution, and a magnesium chloride solution is added to obtain a lead mixed solution; S3: preparing a hydrogel for adsorbing lead The coconut shell is dried, crushed, sieved, soaked in hydrochloric acid, washed and dried to obtain coconut shell powder. The coconut shell powder is dispersed in a pre-cooled liquid, centrifuged, and the supernatant is separated to obtain a coconut shell lignocellulose solution. The coconut shell lignocellulose solution, sodium alginate and cucurbiture solution are mixed and stirred uniformly. APS initiator and MBA crosslinking agent are added, and a hydrogel for adsorbing lead is obtained by gelation. S4: Recycling lead by using the hydrogel for adsorbing lead The hydrogel for adsorbing lead is immersed in a lead mixed solution for adsorption to obtain a saturated hydrogel for adsorbing lead. The saturated hydrogel for adsorbing lead is loaded into an acid-resistant glass column, and nitric acid solution is pumped in for desorption. NaOH solution and sodium carbonate solution are added to the desorption liquid, and stirred until white precipitate is generated. The precipitate is separated by centrifugation, and the filter cake is washed with deionized water until neutral. After drying, a crude PbCO3 product is obtained. After calcination, the recycling of lead is completed.

[0006] Further, the step S1 of leaching the lead refining alkaline residue includes the following steps: The lead refining alkaline residue is soaked in a NaOH solution with a concentration of 100-105 g / L. The solid-liquid ratio is 1 g:(3-5) mL, the temperature is 60-65°C, and the leaching time is 1.5-2 h. After the reaction is completed, the solid particles are filtered out using a 100-mesh stainless steel screen. The sieved slurry is subjected to solid-liquid separation using a suction filter bottle to obtain leaching residue and leaching liquid.

[0007] Further, the step S2 of flocculating the lead residue and preparing a lead mixed solution includes the following steps: The mercapto lignin powder is dissolved in deionized water to prepare a mercapto lignin solution with a concentration of 1-2 wt%. The stirring speed is 200-300 rpm, and the activation time is 30-35 min. The mercapto lignin solution is added to the leaching liquid at a dosage of 0.5-1.5 g / L. The stirring speed is 300-400 rpm, and the stirring time is 10-15 min. A polyacrylamide solution with a mass fraction of 5-10% in the system is then added, and the stirring speed is 50-100 rpm. The stirring time is 5-10 min, and the system is then allowed to stand for 20-30 min. The lead residue is obtained by centrifugal separation. The lead residue and the leaching residue are combined to obtain treated lead residue. The treated lead residue is immersed in a hydrochloric acid solution with a concentration of 2-4 mol / L. The liquid-solid ratio is 1 g:(4-6) mL, the temperature is 85-90°C, and the leaching time is 3-4 h. A magnesium chloride solution with a mass fraction of 15-20% in the system is then added, and the pH value is controlled at 1.5-2 to obtain a lead mixed solution.

[0008] Further, the step S3 of preparing the hydrogel for adsorbing lead includes the following steps: The coconut shell is dried, crushed, and sieved through an 80-mesh screen. The obtained powder is soaked in hydrochloric acid for 24-25 h, washed with deionized water, and dried to obtain coconut shell powder. The coconut shell powder is dispersed in a pre-cooled liquid cooled to 0-2°C, and centrifuged at a speed of 8000-8100 rpm for 10-15 min. The supernatant is separated to obtain a coconut shell lignocellulose solution. The coconut shell lignocellulose solution, sodium alginate and cucurbituril solution are mixed in a volume ratio of (2-2.5):1:1, stirred uniformly, 0.25-0.5 mol% of APS initiator and 1.5-2 mol% of MBA crosslinking agent are added, stirred for 10-15 min, and then transferred to a reactor, the reactor is sealed and heated uniformly in a water bath at 70-75 DEG C for 3-3.5 h to complete the gelation process, and the lead adsorbed hydrogel is obtained.

[0009] Further, the step S4 recovers lead by using the lead adsorbed hydrogel, comprising the following steps: The lead adsorbed hydrogel is immersed in a lead mixed solution, the solid-liquid ratio is 1g:(20-25)mL, and a 50-60 rpm shaking table is oscillated for 3-4 h to obtain a saturated adsorption hydrogel; The saturated adsorption hydrogel is loaded into an acid-resistant glass column, a 0.8-1 mol / L nitric acid solution is pumped in at a flow rate of 2-3 BV / h, the temperature is controlled at 25-30 DEG C, and the desorption is continued for 2-3 h, NaOH solution is slowly added to the desorption solution, the pH is adjusted to 8.5-9, then sodium carbonate solution is added, and stirring is performed until white precipitate is generated, a centrifuge is used to centrifuge at a speed of 3000-3100 rpm for 10-15 min, the precipitate is separated, the filter cake is washed to neutral with deionized water, and after drying, a PbCO3 crude product is obtained, and the PbCO3 is placed in a muffle furnace, heated to 600-650 DEG C and calcined for 2-2.5 h to complete the recovery of lead.

[0010] Further, the content of the mercapto group in the mercaptolignin is 2-3 mmol / g.

[0011] Further, the concentration of the magnesium chloride solution is 5-6 mol / L.

[0012] Further, the pre-cooling liquid is prepared by mixing NaOH, urea and water in a mass ratio of 7:(12-13):(80-85).

[0013] Further, the filling density of the saturated adsorption hydrogel is 0.4-0.6 g / mL.

[0014] Compared with the prior art, the present application has at least the following beneficial effects: 1. The present application uses the hydrogel prepared from coconut shell, cucurbituril and sodium alginate to adsorb lead ions, the porous framework of coconut shell lignocellulose forms three-dimensional through pores, the rich groups on the surface provide physical adsorption sites, accelerate the diffusion of Pb 2+ and improve the water holding capacity of the gel, the carboxyl groups on the sodium alginate are ionized in the solution, form a stable five-membered ring chelate with Pb 2+ through lone pair electrons, and the hydrophobic cavity of cucurbituril is embedded in the micropore edge of lignocellulose through van der Waals force, and Pb 2+The hydrated ion diameter of the lead ion is highly matched with the hydrated ion diameter of the water, and the water is preferentially allowed to hydrate the lead 2+ The water gel and the lead ion are selectively captured by the host-guest interaction, thereby effectively inhibiting the competition of interfering ions such as calcium and magnesium, and improving the saturated adsorption capacity of the water gel to lead, so as to improve the lead content in the lead mixed solution in the early stage, and lay a foundation for subsequent lead recovery.

[0015] 2、The present application combines complexed mercaptolignin with polyacrylamide to flocculate lead residue, significantly improving lead recovery efficiency, and high-density mercaptolignin in mercaptolignin is preferentially combined with Pb 2+ to form a stable complex, realizing molecular-level selective capture of lead ions, effectively avoiding competitive adsorption of coexisting ions such as calcium and zinc, efficiently enriching lead, and at the same time, the long-chain molecules of polyacrylamide play a bridging role, promoting the rapid aggregation and growth of micron-sized lead-mercapto complex particles, overcoming the bottleneck that colloidal lead residue is difficult to settle in traditional precipitation methods, thereby improving the lead precipitation rate and flocculation settling speed, increasing the lead content in the lead residue, greatly reducing the subsequent acid leaching burden, avoiding the introduction of interfering ions such as iron and aluminum, and improving the purity of the subsequent lead carbonate precipitate.

[0016] 3、The present application uses a water gel to adsorb lead, and then uses dilute nitric acid to dynamically desorb, and the desorption liquid is adjusted by pH to make Pb 2+ transformed into Pb(OH)2colloid, and then sodium carbonate is added to generate PbCO3precipitate, thereby efficiently desorbing lead ions by ion exchange, avoiding the destruction of glycosidic bonds and crosslinking networks of the water gel by using strong acid in the traditional leaching method, and enabling the water gel material to be repeatedly used, while the use of the traditional strong acid leaching method leads to the one-time scrapping of the adsorbent, and the lead concentration in the desorption liquid obtained by the water gel adsorption and desorption is high, so that electrolysis is not needed to consume additional power and resources to selectively extract lead with high purity, and only simple and rapid leaching is needed to obtain lead-containing precipitate with high purity, and the lead oxide product is directly obtained by calcination, thereby achieving higher recovery rate and good economic benefit, and the process is more resource-saving and environmentally friendly. BRIEF DESCRIPTION OF DRAWINGS

[0017] The accompanying drawings, which are incorporated herein and constitute part of the specification, illustrate embodiments of the present disclosure and, together with the description, further serve to explain the principles of the present disclosure and to enable a person skilled in the relevant art to implement and use the present disclosure.

[0018] Figure 1 A high-efficiency recovery process flowchart based on lead refining alkaline residue is adopted in the embodiments of the present application. DETAILED DESCRIPTION

[0019] A high-efficiency recovery process based on lead refining alkali slag is described in detail below in combination with the accompanying drawings and specific examples. It is noted here that in order to make the examples more detailed, the following examples are the best, preferred examples, and other alternative ways can also be used by those skilled in the art for some known technologies; and the drawings are only for more specific description of the examples, and are not intended to specifically limit the present application.

[0020] Example 1: A high-efficiency recovery process based on lead refining alkali slag, as shown in Figure 1 includes the following steps: S1: leaching of lead refining alkali slag 1 kg of lead refining alkali slag was soaked in a NaOH solution with a concentration of 100 g / L, the solid-liquid ratio was 1 g:3 mL, the temperature was 60℃, and the leaching time was 1.5 h. After the reaction was completed, the solid particles were filtered out using a 100 mesh stainless steel screen, and the slurry after sieving was subjected to solid-liquid separation using a suction filter bottle to obtain leaching residue and leaching liquor; S2: flocculation of lead slag and preparation of lead mixed solution The mercapto lignin powder was dissolved in deionized water to prepare a 1 wt% mercapto lignin solution, the mercapto content in the mercapto lignin was 2 mmol / g, the stirring speed was 200 rpm, and the activation time was 30 min. The mercapto lignin solution was added to the leaching liquor at a dosage of 0.5 g / L, stirred at 300 rpm for 10 min, then 5% polyacrylamide solution was added to the system, stirred at 50 rpm for 5 min, and then left to stand for 20 min. The lead slag was obtained by centrifugal separation, and the lead slag and leaching residue were combined to obtain treated lead slag. The treated lead slag was immersed in a hydrochloric acid solution with a concentration of 2 mol / L, the liquid-solid ratio was 1 g:4 mL, the temperature was 85℃, and the leaching time was 3 h. Then 15% magnesium chloride solution with a concentration of 5 mol / L was added to the system, and the pH value was controlled at 1.5 to obtain the lead mixed solution.

[0021] S3: preparation of lead-absorbed hydrogel The coconut shell was dried, crushed, and sieved through an 80 mesh screen. The obtained powder was soaked in hydrochloric acid for 24 h, then washed with deionized water and dried to obtain coconut shell powder. The coconut shell powder was dispersed in a pre-cooled liquid pre-cooled to 0℃, and centrifuged at a speed of 8000 rpm for 10 min. The supernatant was separated to obtain a coconut shell lignin fiber solution. The coconut shell lignin fiber solution, sodium alginate, and cucurbiture solution were mixed in a volume ratio of 2:1:1 and stirred uniformly. 0.25 mol% of APS initiator and 1.5 mol% of MBA crosslinking agent were added, stirred for 10 min, and then transferred to a reactor. After the reactor was sealed, it was uniformly heated in a water bath at 70℃ for 3 h to complete the gelation process, and the lead-absorbed hydrogel was obtained.

[0022] S4: Recycling lead by using lead-adsorbed hydrogel The lead-adsorbed hydrogel was immersed in a lead mixed solution with a solid-liquid ratio of 1 g:20 mL, and shaken at 50 rpm for 3 h to obtain a saturated lead-adsorbed hydrogel; The saturated lead-adsorbed hydrogel was loaded into an acid-resistant glass column, and the packing density of the saturated lead-adsorbed hydrogel was 0.4 g / mL. A 0.8 mol / L nitric acid solution was pumped into the column at a flow rate of 2 BV / h, and the temperature was controlled at 25°C for 2 h. NaOH solution was slowly added to the desorption solution to adjust the pH to 8.5, and then sodium carbonate solution was added. After stirring, white precipitate was generated. The precipitate was separated by centrifugation at 3000 rpm for 10 min. The filter cake was washed with deionized water until it was neutral. After drying, a PbCO3 crude product was obtained. The PbCO3 was placed in a muffle furnace and calcined at 600°C for 2 h to complete the recycling of lead.

[0023] The pre-cooling liquid was prepared by mixing NaOH, urea and water in a mass ratio of 7:12:80.

[0024] Example 2: A high-efficiency recycling process based on lead refining alkali residue, as shown in Figure 1 The process comprises the following steps: S1: Leaching of lead refining alkali residue 1 kg of lead refining alkali residue was soaked in a 105 g / L NaOH solution with a solid-liquid ratio of 1 g:5 mL at a temperature of 60°C for 1.5 h. After the reaction, the solid particles were filtered out using a 100-mesh stainless steel screen. The slurry after sieving was subjected to solid-liquid separation using a suction filter bottle to obtain leaching residue and leaching solution. S2: Flocculation of lead residue and preparation of lead mixed solution The mercapto lignin powder was dissolved in deionized water to prepare a 2 wt% mercapto lignin solution. The mercapto content of the mercapto lignin was 3 mmol / g. The stirring speed was 200 rpm, and the activation time was 30 min. The mercapto lignin was added to the leaching solution at a dosage of 1.5 g / L. The stirring speed was 300 rpm, and the stirring time was 10 min. A polyacrylamide solution with a mass fraction of 5% was then added to the system, and the stirring speed was 50 rpm for 5 min. The system was then allowed to stand for 20 min, and the lead residue was obtained by centrifugal separation. The lead residue and the leaching residue were combined to obtain treated lead residue. The treated lead residue was immersed in a 2 mol / L hydrochloric acid solution with a liquid-solid ratio of 1 g:6 mL at a temperature of 85°C for 3 h. A 6 mol / L magnesium chloride solution with a mass fraction of 20% was then added to the system to control the pH value at 1.5, and a lead mixed solution was obtained.

[0025] S3: Preparation of lead-adsorbed hydrogel The coconut shell was dried and crushed, and the obtained powder was immersed in hydrochloric acid for 24 h, then washed with deionized water and dried to obtain coconut shell powder. The coconut shell powder was dispersed in a pre-cooling liquid cooled to 0°C, and centrifuged at a speed of 8000 rpm for 10 min. The supernatant was separated to obtain a coconut shell lignin fiber solution. The coconut shell lignin fiber solution, sodium alginate and cucurbituril solution were mixed in a volume ratio of 2.5:1:1, stirred uniformly, and 0.5 mol% of APS initiator and 2 mol% of MBA crosslinking agent were added. After stirring for 10 min, it was transferred to a reactor, which was sealed and uniformly heated in a water bath at 70°C for 3 h to complete the gelation process, and a lead adsorbed hydrogel was obtained.

[0026] S4: Recycling lead using lead adsorbed hydrogel The lead adsorbed hydrogel was immersed in a lead mixed solution with a solid-liquid ratio of 1g:25mL, and simultaneously oscillated in a 50rpm shaker for 3h to obtain a saturated adsorption hydrogel; The saturated adsorption hydrogel was loaded into an acid-resistant glass column, and the packing density of the saturated adsorption hydrogel was 0.6g / mL. A 1mol / L nitric acid solution was pumped in at a flow rate of 2BV / h, and the temperature was controlled at 25°C. Desorption was continued for 2h, NaOH solution was slowly added to the desorption liquid, and the pH was adjusted to 8.5. Subsequently, sodium carbonate solution was added, and stirring was performed until white precipitate was formed. A centrifuge was used at a speed of 3000rpm for 10 min to separate the precipitate. The filter cake was washed with deionized water until it was neutral. After drying, PbCO3 crude product was obtained. PbCO3 was placed in a muffle furnace and calcined at 600°C for 2h to complete the recycling of lead.

[0027] The pre-cooling liquid was prepared by mixing NaOH, urea and water in a mass ratio of 7:13:85.

[0028] Example 3: A high-efficiency recycling process based on lead refining alkali residue, as shown in Figure 1 The process includes the following steps: S1: Leaching of lead refining alkali residue 1kg of lead refining alkali residue was soaked in a NaOH solution with a concentration of 100g / L, the solid-liquid ratio was 1g:3mL, the temperature was 65°C, and the leaching time was 2h. After the reaction, the solid particles were filtered out using a 100 mesh stainless steel screen. The slurry after sieving was subjected to solid-liquid separation using a suction filter bottle to obtain leaching residue and leaching liquid. S2: Flocculation of lead residue and preparation of lead mixed solution The thiol group lignin powder was dissolved in deionized water to prepare a thiol group lignin solution with a concentration of 1 wt%, the thiol group content of the thiol group lignin was 2 mmol / g, the stirring speed was 300 rpm, the activation time was 35 min, the dosage was 0.5 g / L, the stirring speed was 400 rpm, and the stirring time was 15 min, then 5% of the system mass of polyacrylamide solution was added, the stirring speed was 100 rpm, the stirring time was 10 min, and the standing time was 30 min, then the lead residue was obtained by centrifugal separation, the lead residue and the leaching residue were combined, and the treated lead residue was obtained; The treated lead residue was immersed in a hydrochloric acid solution with a concentration of 4 mol / L, the liquid-solid ratio was 1 g:4 mL, the temperature was 90°C, and the immersion time was 4 h, then 15% of the system mass of magnesium chloride solution with a concentration of 5 mol / L was added, and the pH value was controlled at 2, and the lead mixed solution was obtained.

[0029] S3: Preparation of lead-adsorbed hydrogel The coconut shell was dried, crushed, and sieved through an 80-mesh sieve, the obtained powder was soaked in hydrochloric acid for 25 h, then washed with deionized water and dried to obtain coconut shell powder, the coconut shell powder was dispersed in a pre-cooled liquid pre-cooled to 2°C, and centrifuged at a speed of 8100 rpm for 15 min, the supernatant was separated to obtain a coconut shell lignocellulose solution; The coconut shell lignocellulose solution, sodium alginate, and cucurbiture solution were mixed at a volume ratio of 2.5:1:1, stirred uniformly, 0.5 mol% of APS initiator and 2 mol% of MBA crosslinking agent were added, stirred for 15 min, then transferred to a reactor, the reactor was sealed, and uniformly heated in a water bath at 75°C for 3.5 h to complete the gelation process, and the lead-adsorbed hydrogel was obtained.

[0030] S4: Recycling of lead by using the lead-adsorbed hydrogel The lead-adsorbed hydrogel was immersed in the lead mixed solution, the solid-liquid ratio was 1 g:20 mL, and the shaking table was oscillated at 60 rpm for 4 h to obtain the saturated lead-adsorbed hydrogel; The saturated lead-adsorbed hydrogel was loaded into an acid-resistant glass column, the packing density of the saturated lead-adsorbed hydrogel was 0.4 g / mL, a nitric acid solution with a concentration of 0.8 mol / L was pumped in at a flow rate of 3 BV / h, the temperature was controlled at 30°C, and the desorption was continued for 2 h, NaOH solution was slowly added to the desorption solution, the pH value was adjusted to 9, then sodium carbonate solution was added, stirred until white precipitate was formed, the centrifuge was used to centrifuge the precipitate at a speed of 3100 rpm for 15 min, the precipitate was separated, the filter cake was washed with deionized water until neutral, dried to obtain a PbCO3 crude product, the PbCO3 was placed in a muffle furnace, heated to 650°C, and calcined for 2.5 h to complete the recycling of lead.

[0031] The pre-cooled liquid was prepared by mixing NaOH, urea, and water at a mass ratio of 7:12:80.

[0032] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that no mercaptan lignin powder is added in step S2, and the remaining steps are unchanged, which is denoted as Comparative Example 1.

[0033] Comparative Example 2: The difference between Comparative Example 2 and Example 1 is that no polyacrylamide is added in step S2, and the remaining steps are unchanged, which is denoted as Comparative Example 2.

[0034] Comparative Example 3: The difference between Comparative Example 3 and Example 1 is that no cucurbituril solution is added in step S3, and the remaining steps are unchanged, which is denoted as Comparative Example 3.

[0035] Comparative Example 4: The difference between Comparative Example 4 and Example 1 is that no sodium alginate is added in step S3, and the remaining steps are unchanged, which is denoted as Comparative Example 4.

[0036] Comparative Example 5: The difference between Comparative Example 5 and Example 1 is that the lead refining alkaline residue is leached by leaching method, specifically: “1 kg of lead refining alkaline residue is leached with 15% hydrochloric acid, and hydrogen peroxide is added, the liquid-solid ratio is 5:1, the temperature is 60℃, the reaction time is 1.5h, the pH value is 1.5, the stirring speed is 200rpm, and the leaching residue is separated by filtration and converted into a precipitate with sodium carbonate solution”, which is denoted as Comparative Example 5.

[0037] Comparative Example 6: The difference between Comparative Example 6 and Example 1 is that the lead in the lead refining alkaline residue is recovered by electrolysis, specifically: “the current density is 300A / m 2 , 1 kg of lead refining alkaline residue is electrolyzed, and the lead component is converted into Na2[Pb(OH)4] in the electrolysis, the temperature is 105℃; the electrolyte enters the cation exchange membrane electrolytic cell, and the metal lead is generated in the cathode chamber, and the oxygen and NaOH are by-produced in the anode chamber; Cathode reaction: Pb(OH)4 2- + 2e - → Pb + 4OH - Anode reaction: 4OH - → O2↑ + 2H2O + 4e - The lead is obtained in the cathode”, which is denoted as Comparative Example 6.

[0038] The lead content in the lead mixed solution obtained in step S2 of Examples 1-3 and Comparative Examples 1-2 is detected, as shown in Table 1; The extraction rate and purity of PbCO3 obtained in step S4 of Examples 1-3 and Comparative Examples 3-4 are detected respectively, as shown in Tables 2 and 3; The lead content in the lead refining alkali residue of Examples 1-3 and Comparative Examples 5-6 was tested, the purity and weight of the final lead carbonate were tested, and the lead recovery rate was calculated. The Pb content in PbCO3 was recorded as 77.6%, and the mass of the lead refining alkali residue was 1 kg. The results are shown in Table 4.

[0039] In Examples 1-3 and Comparative Example 5, the lead recovery rate (%) = (lead carbonate purity * lead carbonate mass * 77.6%) / (lead content in lead refining alkali residue * lead refining alkali residue mass). In Comparative Example 6, the lead recovery rate (%) = mass of elemental lead / (lead content in lead refining alkali residue * mass of lead refining alkali residue). The lead refining alkali residue used in the above examples and comparative examples was from the same batch. Each group was tested three times, and the average value of the obtained data was taken.

[0040] Table 1

[0041] Table 2

[0042] Table 3

[0043] Table 4

[0044] As can be seen from Table 1, the lead content of Comparative Example 1 lacking mercaptolignin and Comparative Example 2 lacking polyacrylamide dropped from more than 98 mg / mL to less than 88 mg / mL and less than 90 mg / mL, respectively. This indicates that the two components synergistically complex and flocculate lead ions in step S2, and the lack of either one significantly reduces the collection efficiency.

[0045] As shown in Tables 2 and 3, the PbCO3 extraction rates of Comparative Example 3 (lacking cucurbitacin solution) and Comparative Example 4 (lacking sodium alginate) decreased from over 95.7% to 82.3% and 84.1%, respectively, and the purity also dropped from over 99% to below 96%. This indicates that these two components, together with coconut shell lignin fibers in step S3, selectively encapsulate and gel-fix Pb. 2+ It has the effect of inhibiting the co-precipitation of impurities.

[0046] As shown in Table 4, the lead recovery rate of Examples 1-3 remained stable at around 95.5%; while that of Comparative Example 5, which used conventional 15% hydrochloric acid leaching, was only 85.3%, and that of Comparative Example 6, which used traditional electrolysis, was only 92.7%. This indicates that the recovery efficiency of lead refining alkali slag under the three-stage process of "capture-precipitation-conversion" is significantly better than that of a single wet process or electrolysis process.

[0047] The above embodiments are only illustrative of the principles of the present application and its efficacy, and are not intended to limit the present application. Any modification or change made by any person skilled in the art without departing from the spirit and scope of the present application shall be covered by the claims of the present application.

Claims

1. A high-efficiency recovery process based on lead refining alkali slag, characterized in that, Includes the following steps: S1: Leaching of lead refining alkali residue The lead refining alkali residue was soaked in NaOH solution. After the reaction was completed, the solid particles were filtered out using a 100-mesh stainless steel sieve. Solid-liquid separation was performed to obtain leaching residue and leaching solution. S2: Flocculating lead slag and preparing lead mixture Mercaptolignin powder was dissolved in deionized water to prepare a mercaptolignin solution. The solution was stirred and activated, then added to the leachate. After stirring, polyacrylamide solution was added, stirred, and centrifuged to obtain lead slag. The lead slag and leachate residue were combined to obtain treated lead slag. The treated lead slag was then immersed in hydrochloric acid solution, and magnesium chloride solution was added to obtain a lead mixed solution. S3: Preparation of lead-adsorbed hydrogels After drying, the coconut shells are crushed, sieved, soaked in hydrochloric acid, washed and dried to obtain coconut shell powder. The coconut shell powder is dispersed in a pre-cooled liquid, centrifuged, and the supernatant is separated to obtain a coconut shell wood fiber solution. The coconut shell wood fiber solution, sodium alginate, and cucurbituril solution are mixed and stirred evenly. APS initiator and MBA crosslinking agent are added, and gelation is performed to obtain a lead-adsorbed hydrogel. S4: Lead recovery using lead-adsorbing hydrogels The lead-adsorbing hydrogel was immersed in a lead-containing mixed solution for adsorption, resulting in a saturated hydrogel. The saturated hydrogel was then packed into an acid-resistant glass column, and nitric acid solution was pumped in for desorption. NaOH solution and sodium carbonate solution were added to the desorption solution, and the mixture was stirred until a white precipitate was formed. The precipitate was separated by centrifugation, and the filter cake was washed with deionized water until neutral. After drying, crude PbCO3 was obtained, which was then calcined to complete the lead recovery.

2. The efficient recovery process based on lead refining alkali slag according to claim 1, characterized in that, Step S1 involves leaching the lead refining alkali residue, including the following steps: The lead refining alkali residue was soaked in a NaOH solution with a concentration of 100-105 g / L, the solid-liquid ratio was 1 g: (3-5) mL, the temperature was 60-65℃, and the leaching time was 1.5-2 h. After the reaction was completed, the solid particles were filtered out using a 100-mesh stainless steel sieve. The slurry after sieving was then separated into solid and liquid by vacuum filtration to obtain leaching residue and leaching liquid.

3. The efficient recovery process based on lead refining alkali slag according to claim 2, characterized in that, Step S2, flocculating lead slag and preparing lead mixed solution, includes the following steps: Dissolve mercaptolignin powder in deionized water to prepare a 1-2 wt% mercaptolignin solution. Stir at 200-300 rpm for 30-35 min and add to the leachate at 0.5-1.5 g / L. Stir at 300-400 rpm for 10-15 min. Then add 5-10% of the system mass of polyacrylamide solution and stir at 50-100 rpm for 5-10 min. Let stand for 20-30 min and centrifuge to obtain lead slag. Combine the lead slag and leachate residue to obtain treated lead slag. The lead slag is immersed in a hydrochloric acid solution with a concentration of 2-4 mol / L, the liquid-to-solid ratio is 1 g: (4-6) mL, the temperature is 85-90℃, and the leaching time is 3-4 h. Then, 15-20% of the system mass of magnesium chloride solution is added, and the pH value is controlled at 1.5-2 to obtain a lead mixture.

4. The efficient recovery process based on lead refining alkali slag according to claim 3, characterized in that, Step S3 involves preparing a lead-adsorbed hydrogel, which includes the following steps: After drying the coconut shell, crush it and pass it through an 80-mesh sieve. Soak the obtained powder in hydrochloric acid for 24-25 hours, then wash and dry it with deionized water to obtain coconut shell powder. Disperse the coconut shell powder in a pre-cooled liquid pre-cooled to 0-2℃ and centrifuge it at 8000-8100 rpm for 10-15 minutes. Separate the supernatant to obtain a coconut shell wood fiber solution. Coconut shell lignocellulose solution, sodium alginate, and cucurbituril solution were mixed and stirred evenly at a volume ratio of (2-2.5):1:

1. 0.25-0.5 mol% APS initiator and 1.5-2 mol% MBA crosslinking agent were added. After stirring for 10-15 min, the mixture was transferred to a reactor. The reactor was sealed and heated uniformly in a water bath at 70-75℃ for 3-3.5 h to complete the gelation process and obtain a lead-adsorbed hydrogel.

5. The efficient recovery process based on lead refining alkali slag according to claim 4, characterized in that, Step S4 utilizes a lead-adsorbing hydrogel to recover lead, including the following steps: The hydrogel that adsorbs lead is immersed in a lead mixture at a solid-liquid ratio of 1g:(20-25)mL, and simultaneously shaken on a shaker at 50-60rpm for 3-4h to obtain a hydrogel that is saturated with adsorption. The saturated hydrogel was packed into an acid-resistant glass column, and a 0.8-1 mol / L nitric acid solution was pumped in at a flow rate of 2-3 BV / h. The temperature was controlled at 25-30℃, and desorption was continued for 2-3 hours. NaOH solution was slowly added to the eluent to adjust the pH to 8.5-9, followed by the addition of sodium carbonate solution. The mixture was stirred until a white precipitate was formed. The precipitate was separated by centrifuging at 3000-3100 rpm for 10-15 minutes. The filter cake was washed with deionized water until neutral and dried to obtain crude PbCO3. The PbCO3 was then placed in a muffle furnace and calcined at 600-650℃ for 2-2.5 hours to complete the lead recovery.

6. The efficient recovery process based on lead refining alkali slag according to claim 3, characterized in that, The thiol content in thiol lignin is 2-3 mmol / g.

7. The efficient recovery process based on lead refining alkali slag according to claim 3, characterized in that, The concentration of the magnesium chloride solution is 5-6 mol / L.

8. The efficient recovery process based on lead refining alkali slag according to claim 4, characterized in that, The precooling liquid is prepared by mixing NaOH, urea and water in a mass ratio of 7:(12-13):(80-85).

9. The efficient recovery process based on lead refining alkali slag according to claim 5, characterized in that, The filling density of the adsorbed saturated hydrogel is 0.4-0.6 g / mL.

Citation Information

Patent Citations

  • Method for recovering lead from lead-containing solid wastes

    CN103290225A

  • Sodium alginate / carboxylated cellulose nanocrystal hydrogel microsphere for adsorbing lead ions

    CN108014760A

  • Lead slag secondary recovery process

    CN117758051A

  • Prepn. of znso4 and active zno from zinc ore by entire wet-process

    CN86108798A

  • Deleading method of molten slag

    JP2001089203A